Water Flow and Light Availability Influence on Intracellular Geosmin Production in River Biofilms - Espinosa, Carmen; Abril, Meritxell; Guasch, Helena; Pou, Núria; Proia, Lorenzo; Ricart, Marta; Ordeix, Marc; Llenas, Laia (Frontiers in Microbiology, 2020)
Hydro-morphological alterations in water bodies caused by climate change and human activities affects the ecosystem functioning and generate important water quality problems. Some of these alterations can generate an increase in cyanobacterial blooms, which are associated with the appearance of bad taste and odorous compounds such as geosmin. The factors that trigger their production are still unclear, and this inability to predict geosmin episodes provokes economic problems for water supply companies. This study aims to evaluate the effects of water flow and light availability on biofilm development and intracellular geosmin formation. A mesocosm experiment was performed between February – April 2019. The mesocosms were a set of 10 outdoor 3m long flumes, with a continuous water supply from the Ter river (Catalonia, NE Spain). Two light intensities were established: natural light and light reduced to 80%, combined with five gradual water flows from 0.09 to 1.10 L/s. Water samples were taken to analyse nutrients, and biofilm samples, to analyse geosmin concentration, Chlorophyll a and the community. Geosmin in biofilm was detected in those treatments in which Oscillatoria sp. appeared. The concentration of intracellular geosmin was higher at lower water flows (0.09 and 0.18 L/s), and the highest (2.12 mg/g) was found in the flume with the lowest water flow (0.09 L/s) and irradiation (20%). This flume was the one that presented a greater concentration of Oscillatoria sp. (21% of the community). It stands out that, when geosmin in biofilm was found, the dissolved inorganic nitrogen and soluble reactive phosphorus ratio decreased, from an average of 417:1 to 14:1. This was mainly due to an increase in inorganic phosphorus concentration generated by a change in the nutrient uptake capacity of the community’s biofilm. The results obtained in this study indicated the potential implications for stream ecosystem management to control geosmin appearance. Likewise, they could be used as an early warning system, establishing that in times of drought, which lead to a general decrease in river water flow, the situation could be optimal for the appearance and development of geosmin producing cyanobacteria in low-flow areas near the river banks.